2007
DOI: 10.1177/0142723707067545
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative aspects of productive vocabulary at the 200-and 500-word stages: A comparison between spontaneous speech and parental report data

Abstract: This paper compares the proportions of different word classes present in 30 Italian children at two specific stages of vocabulary development (200 and 500 words). The Italian version of the MacArthur Communicative Development Inventory and spontaneous speech samples produced during an observation session were both used to examine the extent to which these children produce quantitatively different vocabulary compositions. Both methods revealed a greater presence of nouns than other word classes in the sample st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 25 publications
3
28
0
Order By: Relevance
“…Verbs, and verb-like items, are acquired later as they involve more cognitively complex tasks for children to accomplish. This account has been supported by a great number of studies in various languages (in English by Bornstein et al, 2004;Fenson et al, 1993;Goldfield, 2000, in Italian by Bornstein et al, 2004;Caselli et al, 1995;Salerni, Assanelli, D'Odorico, & Rossi, 2007;Tardif, Shatz, & Naigles, 1997, in Hebrew by Bornstein et al, 2004;Dromi, 1987;Maital, Dromi, Sagi, & Bornstein, 2000, in Spanish by Jackson-Maldonado, Thal, Marchman, Bates, & Guitierrez-Clellen, 1993and in Dutch, Bornstein et al, 2004De Houwer & Gillis, 1998;Verlinden & Gillis, 1988). However, researchers challenging this view claim that the characteristics of any language being acquired are as important as cognitive factors.…”
Section: Introductionmentioning
confidence: 83%
“…Verbs, and verb-like items, are acquired later as they involve more cognitively complex tasks for children to accomplish. This account has been supported by a great number of studies in various languages (in English by Bornstein et al, 2004;Fenson et al, 1993;Goldfield, 2000, in Italian by Bornstein et al, 2004;Caselli et al, 1995;Salerni, Assanelli, D'Odorico, & Rossi, 2007;Tardif, Shatz, & Naigles, 1997, in Hebrew by Bornstein et al, 2004;Dromi, 1987;Maital, Dromi, Sagi, & Bornstein, 2000, in Spanish by Jackson-Maldonado, Thal, Marchman, Bates, & Guitierrez-Clellen, 1993and in Dutch, Bornstein et al, 2004De Houwer & Gillis, 1998;Verlinden & Gillis, 1988). However, researchers challenging this view claim that the characteristics of any language being acquired are as important as cognitive factors.…”
Section: Introductionmentioning
confidence: 83%
“…However, further research on this field, especially intercultural studies, will be needed to draw a bigger picture on this issue. Intercultural studies provide evidence that the acquisition of nouns, particularly in early speech development, plays a significant role compared to the verb and the other word classes (Werning, 2008); the word class of nouns is predominant in speech production (e.g., Salerni, Assanelli, D’Odorico, & Rossi, 2007) and speech comprehension. In another intercultural study over seven different oral cultures, findings showed that 20-months old children have more nouns at their command than any other word class in their vocabulary (Bornstein et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Our full corpus thus comprises 5000 utterances. For Italian, we used 500-utterance-long samples from the utterances of 10 adults from four Italian language subcorpora (Antelmi, 2004; Antinucci and Parisi, 1973; Cipriani et al, 1989; Tonelli et al, 1995; Salerni et al, 2007) of the CHILDES database (MacWhinney, 2000). The full corpus comprises 5000 utterances.…”
Section: Methodsmentioning
confidence: 99%